Pseudonegligência, dominância manual e habilidades motoras em alunos das artes em comparação com alunos de outros cursos - MELO, Thiago Martins de (2008)
A prominent line of research dealing with cerebral lateralization in artists have investigated the behavior of artists afflicted with various neuropathological syndromes affecting either the right or left hemisphere. In contrast, Bertrand (2001), noting that a few studies have reported an increased prevalence of left-handedness and ambidextrality among artists, suggested the need for systematic research into the laterality characteristics of normal artists. In the absence of such studies, and because it was not possible to obtain data from professional artists, this project was designed to investigate in detail, lateral asymmetries in handedness, motor abilities and visuospatial attention in art and non-art students. These students were recruited from the Art Department at the Federal University of Maranhão, and a public school of art in São Luis. There were 50 non-art students (24 right- and 26 left-handers), and 51 art students (27 right- and 24 left-handers) in the sample. Data were obtained on handedness, eyedness, and footedness, and two measures of motor proficiency: Finger tapping and the Grooved Pegboard Test. In addition, a version of the Visual Line Bissection Test (VLBT) was administered in order to compare the degree of pseudonegligence among and between art and non-art students. We sought to ascertain whether, in comparison with non-artists, the art students would evince a reduced degree of intermanual asymmetry in handedness and motor ability, as well as higher-level accuracy on the VLBT. Our predictions regarding such performance differences, were in fact, supported. Art students, especially left-handers were much less consistent, and more ambidextrous than dextral and sinistral non-art students, and displayed a lower between-hand performance on both motor tests. Also, whereas the degree of pseudonegligence was increased among non-art students, art students were more accurate in their responses, and produced fewer errors around the true zero point. Consistent with previous research among musicians, art students in general, showed a balanced level of visuospatial attention, and these differences were related to the cognitive demands of visual art training.